Rancang Bangun Aplikasi Pemilihan Paket Wisata Berbasis Web Pada Paramuda Tour & Transport - Trimaryanto, Bambang; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Paramuda Tour & Transport is a company engaged in travel agency, Customer Paramuda Tour & Transport comes from the area around the company just so that customers outside the area are still not familiar with the companies and products owned. New customers will have trouble choosing travel packages available on the company because customers do not know the customer will get the facilities, attractions, prices and others - others in accordance with what the customer needs.To overcome these problems Paramuda Tour & Transport requires an application that is able to assist customers in the selection of flights, so that customers will get the results on travel packages that fit the criteria of criteria that customers want. Application will be made using AHP, since the AHP method can determine the priority, and AHP also can solve the problems that are multiple criteria such as the selection of tour packages.Application packages selection Paramuda travel on Tour and Transport may determine recommended travel packages based on the desired criteria customers with AHP method. Applications can also provide the latest information on products available on the company to customers, so that customers can choose the travel packages as desired.